Sistema de gestión de información para cultivos cíclicos de flores de corte en la sabana de occidente de Cundinamarca (2022)
In this project express the process of investigation and development of an information system that help to an expert in sector floricultural to make the process of data, the handling of the information and generation of reports, based on cycle vegetative generated between the process of sowing, monitoring phenological and classification of product vegetable, that will allow to the floricultural classify the variety with the best results in the process